Metal-organic frameworks for gas storage applications - Priest, Scott (2024)
The work presented herein focuses on the continuous synthesis of metal-organic frameworks HKUST-1 and UTSA-16 using a nozzle reactor and Swirl reactor. Optimisations for both metal-organic frameworks were achieved at ambient conditions of 25 oC, 1 bar at lab-scale. Both optimisations were then successfully scaled-up using an industrial continuous flow reactor, the Pilot+ nozzle reactor, followed by the Swirl reactor at Promethean Particles at 1 kg scale, each with high yields of 93.0 and 95.2 % and CO2 uptake performances of 20.1 wt. % and 12.8 wt. % for HKUST-1 and UTSA-16, respectively.